Investigation of ruthenium loaded beta zeolite catalyst performance in vanillin hydrodeoxygenation yielding both monomeric and dimeric cycloalkanes - Park, Jae Hyun; Kim, Hyungjoo; Jung, Hyeongdong; Ha, Jeong-Myeong; Kim, Do Heui (Elsevier BV, 2024)
The valorization of lignin-derived bio-oil is studied extensively due to its promising contribution to sustainability. Among these studies, many have focused on the hydrodeoxygenation (HDO) of phenolic model compounds as it is a crucial process in obtaining valuable oxygen-free hydrocarbons. In this work, vanillin HDO was performed on various bifunctional ruthenium-based zeolite catalysts with different zeolite supports (Y, ZSM-5, and beta) in a batch reactor. Ru-loaded beta zeolite catalysts (Ru/H beta) exhibited the highest HDO activity among them, and the formation of dimeric cycloalkanes of high value were also observed specifically when using the Ru/H beta catalyst. Due to their benefits of direct use in blending of biofuel, factors promoting the dimerization of phenolic monomers were extensively examined through a series of experiments using a mix of phenolic model compounds as HDO reactants. Specific oxygen containing functional groups contributed to the aldol condensation of aromatic species, and the structure and kinetic diameter of the monomers had a profound effect on the ability to participate in dimerization. Additionally, the metal loading of the catalyst and reaction conditions such as temperature and hydrogen pressure were varied to observe each of their effects on the product distribution. The change in metal loading had a remarkable impact on the preferred reaction pathway and product selectivity, while a high temperature of 200 degrees C and hydrogen pressure of 50 bar was determined to be necessary to fully achieve HDO to cycloalkanes. Consequently, this study has provided useful information on the production of both monomeric and dimeric cycloalkanes and has contributed to the development of the bio-oil upgrading process.